2017
DOI: 10.1038/ncomms13996
|View full text |Cite
|
Sign up to set email alerts
|

Cell division orientation is coupled to cell–cell adhesion by the E-cadherin/LGN complex

Abstract: Both cell–cell adhesion and oriented cell division play prominent roles in establishing tissue architecture, but it is unclear how they might be coordinated. Here, we demonstrate that the cell–cell adhesion protein E-cadherin functions as an instructive cue for cell division orientation. This is mediated by the evolutionarily conserved LGN/NuMA complex, which regulates cortical attachments of astral spindle microtubules. We show that LGN, which adopts a three-dimensional structure similar to cadherin-bound cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
164
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 133 publications
(187 citation statements)
references
References 51 publications
(88 reference statements)
18
164
2
2
Order By: Relevance
“…We showed previously that LGN binds the cytosolic tail of E-cadherin to stabilize cortical astral microtubule interactions at E-cadherin adhesions and establish planar epithelial divisions (8). Strikingly, we observed that the junctional recruitment of LGN was dependent on cell density:…”
Section: Resultssupporting
confidence: 49%
See 3 more Smart Citations
“…We showed previously that LGN binds the cytosolic tail of E-cadherin to stabilize cortical astral microtubule interactions at E-cadherin adhesions and establish planar epithelial divisions (8). Strikingly, we observed that the junctional recruitment of LGN was dependent on cell density:…”
Section: Resultssupporting
confidence: 49%
“…The cell-cell adhesion protein E-cadherin has a prominent role in orienting cell divisions (8,(26)(27)(28)(29)(30) as well as in sensing tensile forces between neighboring cells (31,32). Tension on E-cadherin junctions can be generated by forces exerted on the extracellular domain by neighboring cells, which can be induced by application of external stretch, and intracellularly through actomyosin contraction (31).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A very recent report (Gloerich et al, 2017) demonstrates that another adherens junction protein, E-cadherin, can also bind directly to LGN. Using a clever cultured cell system, this study shows that E-cadherin recruits LGN to cell-cell contacts and can serve as an instructive cue for spindle orientation.…”
Section: Introductionmentioning
confidence: 99%